FRI0278 OFF-LABEL USE OF BIOLOGICAL THERAPIES IN RELAPSING AND/OR REFRACTORY EOSINOPHILIC GRANULOMATOSIS WITH POLYANGIITIS (CHURG-STRAUSS). (June 2019) - Canzian, Alice; Venhoff, Nils; Sartorelli, Silvia; Ruppert, Anne Marie; Groh, Matthieu; Taille, Camille; Rieu, Virginie; Smets, Perrine; Maurier, Francois; Girszyn, Nicolas; Samson, Maxime; Moreuil, Claire De; et al.
Abstract : Background: Eosinophilic granulomatosis with polyangiitis (EGPA), formerly named Churg-Strauss syndrome, is a small-vessel necrotizing vasculitis associated with eosinophilia and asthma. Glucocorticoids (GCs) usually control the disease, but relapses and GC-dependant asthma are frequent, leading to potential biological therapy use. Objectives: We examined off-label biological therapy use for relapsing/refractory EGPA. Methods: Remission was defined as the absence of asthma and vasculitis manifestations with a prednisone dose ≤5 mg/day, and partial response as the absence of manifestations requiring prednisone dose between 6 and 10 mg/day. Results: One hundred and eigteen patients (66 men, 52 women; median age 50.5 years) were included. Fifty (42%) patients received rituximab (RTX), 38 (32%) mepolizumab (MEPO), and 30 (26%) omalizumab (OMA). Previous treatments were: oral GCs (98%), methylprednisolone infusions (51%), azathioprine (68%), cyclophosphamide (47%), methotrexate (30%), mycophenolate mofetil (8%). At inclusion, median (interquartile range) BVAS in the RTX, OMA and MEPO groups were 8 (4.5-13), 2 (1.5-4) and 2 (2-5), respectively, median (IQR) daily GCs dose were 20 mg/day (15-40), 20 mg/day (10-37.5), 10 mg/day (7.5-20). GC-dependant asthma was found in 39 (78%) of the RTX group, 36 (95%) in the MEPO group and 28 (93%) in the OMA group. After median follow-up of 22.8 months (IQR 10-47), remissions, partial responses and therapeutic failures, respectively, were noted in 50%, 16% and 34% for RTX recipients, 17%, 38% and 45% for the OMA group and 84%, 3% and 13% for the MEPO group. Median BVAS dropped to 0 at 6 and 12 months and at last follow-up in all groups. A GC-sparing effect seemed more important with RTX and MEPO. Median GCs dose decreased from the baseline 20 mg/day to 8.5 at 6 months, 7.5 at 12 months and 5 at last follow-up in the RTX group, from 20 mg/day to 12 at 6 months, 10 at 12 months and 10 at last follow-up in the OMA group, and from 10 mg/day to 5 at 6 months, 3 at 12 months and 5 at last follow-up in the MEPO group. In the MEPO group, no difference was noted between patients receiving 100 mg and those 300 mg monthly.Nine (18%) patients stopped RTX because of refractory disease, and 12 (24%) experienced adverse events, including severe infections in 5. Thirteen (43%) stopped OMA because of severe infusion reaction in one and refractory disease in 12, and 4 (13%) patients receiving OMA experienced adverse events. Three (8%) patients stopped MEPO because of adverse events in 2 (one severe infusion reaction and one because of paresthesia), because of pregnancy in one. Seven (18%) additional patients receiving MEPO experienced adverse events, mainly asthenia. Conclusion: The results suggest that RTX may be effective in 50% of patients with vasculitis relapses related to EGPA, with an acceptable safety profile, while MEPO is highly effective with a good GCs-sparing effect and safety profile in patients with steroid-dependant asthma. Disclosure of Interests: Alice Canzian: None declared, Nils Venhoff: None declared, Silvia Sartorelli: None declared, Anne Marie Ruppert: None declared, Matthieu Groh: None declared, Camille Taille: None declared, Virginie Rieu: None declared, Perrine Smets: None declared, Francois Maurier: None declared, Nicolas Girszyn: None declared, Maxime Samson: None declared, Claire De Moreuil: None declared, Gregory Pugnet: None declared, Xavier Delbrel: None declared, Jean-Emmanuel Kahn: None declared, Xavier Puéchal: None declared, Giacomo Emmi: None declared, Loïc Guillevin: None declared, Lorenzo Dagna Consultant for: Prof Lorenzo Dagna received consultation honoraria from Abbvie, Amgen, Biogen, Bristol-Myers Squibb, Celltrion, Novartis, Pfizer, Sanofi-Genzyme, and SOBI., Jens Thiel: None declared, Augusto Vaglio: None declared, Benjamin Terrier: None declared